Method for degrading organic matters in desulfurized water by dual catalytic oxidation

Through dual-catalytic oxidation and degradation and electrolytic treatment, nano-ferrous supported catalysts and persulfate oxidation reactions in hydrogen peroxide, combined with electrolytic treatment, the problem of difficulty in removing organic matter and iron ions in desulfurization water is solved, and Li2O in lithium hydroxide production is improved Content and production efficiency.

CN119285129AInactive Publication Date: 2025-01-10YAHUA LITHIUM IND (YAAN) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411298612.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has high organic matter and iron content in the desulfurized water during the lithium hydroxide production process, resulting in foam and iron hydroxide colloids produced during slurry adjustment, affecting the Li2O content and production cost of lithium slag.

Method used

The bicatalytic oxidation and degradation method is adopted to carry out an oxidation reaction in hydrogen peroxide by nano-ferrous supported catalyst and persulfate, and combined with electrolytic treatment, a precipitation of chlorophyllium is formed to remove organic matter and iron ions and reduce the formation of iron hydroxide colloids.

Benefits of technology

Effectively degrade organic matter and iron ions in desulfurized water, increase the Li2O content in the leaching liquid, reduce production costs and energy consumption, and avoid the formation of iron hydroxide colloids, and improve the quality of lithium slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285129A_ABST
    Figure CN119285129A_ABST
Patent Text Reader

Abstract

The invention discloses a method for degrading organic matters in desulfurized water through dual catalytic oxidation, and relates to the technical field of desulfurized water treatment. Comprising the following steps: naturally settling desulfurized water, and taking supernate to obtain impurity-removed liquid; adjusting the pH value of the impurity removal liquid to 3-4, adding a nano-iron supported catalyst and persulfate, uniformly mixing, adding hydrogen peroxide, and carrying out an oxidation reaction to obtain oxidized produced water; electrifying the oxidized produced water for electrolysis while continuously stirring and introducing air, and obtaining electrolyzed produced water after the reaction is finished; and adjusting the pH value of the electrolyzed water to 2.0-2.2, reacting to form a sodium jarosite precipitate, and filtering to obtain a treating fluid and sodium jarosite slag. On the basis of a Fenton / persulfate oxidation system, dual catalytic oxidation degradation of the organic matters is realized, the refractory organic matters are further mineralized into carbon dioxide and water through an electrolytic reaction, and a large amount of Fe < 3 + > in the desulfurized water is removed in a manner of forming sodium jarosite precipitate; and ferric hydroxide colloid is prevented from being formed in the subsequent size mixing procedure, so that the content of Li2O in the leachate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of desulfurized water treatment, and in particular to a method for degrading organic matter in desulfurized water using dual catalytic oxidation. Background Art

[0002] At present, the spodumene sulfuric acid method is often used to produce lithium hydroxide. The lithium iron ore is acidified and roasted to convert the lithium in the ore into a form that is easy to extract. In the production process of lithium hydroxide, the metallurgical section desulfurization process will use liquid alkali for desulfurization. In order to ensure the desulfurization effect, this process will produce a large amount of desulfurization water. Since the lithium iron ore contains organic matter, the organic matter will volatilize after calcination in the metallurgical section. After passing through the desulfurization device, a large amount of organic matter and suspended matter will be enriched in the desulfurization water. The desulfurization water containing organic matter will affect the production when it enters the system for use. At present, the Fenton oxidation method is usually used to degrade the organic matter in the desulfurization water, and then the Fenton oxidation water is used to degrade the organic matter in the desulfurization water. The desulfurized water after oxidation treatment is used in the slurry mixing process of the lithium hydroxide production process. However, Fenton oxidation can only degrade most of the organic matter, and some small molecular organic matter will still remain in the solution. In addition, some organic matter that is difficult to degrade in the desulfurized water will produce foam that is difficult to dissipate during slurry mixing, and there is a phenomenon of bubbling; in addition, due to the ferrous sulfate catalyst added in the previous Fenton reaction, the iron content is high, so that more iron hydroxide colloids are produced during slurry mixing. These colloids will absorb and wrap the lithium in the solution, and enter the lithium slag after squeezing, so that the Li2O content in the leachate is lower than the workshop standard, and it needs to be further concentrated before it can be used for production, which will increase production costs and energy consumption. Based on this, the present application proposes a method for dual catalytic oxidation degradation of organic matter in desulfurized water. Summary of the invention

[0003] The main purpose of the present application is to provide a method for dual catalytic oxidation degradation of organic matter in desulfurized water, aiming to solve the technical problem that organic matter in desulfurized water is still difficult to be reused in the slurry preparation process after Fenton oxidation degradation.

[0004] To achieve the above purpose, the present application proposes a method for dual catalytic oxidation degradation of organic matter in desulfurized water, comprising the following steps:

[0005] After the desulfurized water is naturally settled, the supernatant is taken to obtain the impurity-removing liquid;

[0006] After adjusting the pH value of the impurity removal liquid to 3-4, adding the nano-iron supported catalyst and persulfate, mixing well, adding hydrogen peroxide, and performing an oxidation reaction to obtain oxidized water;

[0007] The oxidation-produced water is electrified for electrolysis while continuously stirred and air is introduced, and after the reaction is completed, electrolysis-produced water is obtained;

[0008] The pH value of the electrolytic water is adjusted to 2.0-2.2, and after the reaction forms natrona precipitate, it is filtered to obtain a treated liquid and natrona slag.

[0009] Optionally, the step of taking the supernatant after the desulfurized water is naturally settled to obtain the impurity-removing liquid comprises:

[0010] The desulfurized water is naturally settled at 5°C-35°C for 4h-8h, and after stratification, a supernatant liquid and a lower liquid are obtained by separation;

[0011] The lower layer liquid was stirred in reverse, and then naturally settled again at 5°C-35°C for 2h-4h. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid.

[0012] Optionally, the preparation step of the nano-iron supported catalyst comprises:

[0013] The iron disulfide is pretreated, calcined at 700-800°C for 1h-1.5h, ball-milled at a speed of 180rpm / min-240rpm / min for 5h-7h, and dried to obtain nano iron disulfide particles;

[0014] The graphene is subjected to oxidation treatment and then subjected to derivatization and modification to obtain modified graphene;

[0015] The nano iron disulfide particles, the modified graphene and the polylactic acid are blended in a mass ratio of (1-2): (8-12): (3-5), dried at 110° C.-130° C. for 11 h-13 h, and then screw extruded to obtain a hot-melt filament;

[0016] The hot-melt filament is printed into a honeycomb structure with multiple internal pores by using a fused deposition modeling method, thereby obtaining the nano-iron-loaded catalyst.

[0017] Optionally, the step of oxidizing the graphene and then deriving and modifying it to obtain modified graphene comprises:

[0018] After stirring and mixing graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, the mixture is heated in an oil bath to 75°C-85°C and kept warm for 4.5h-5.5h, cooled to room temperature, filtered and washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and then the product is added to concentrated sulfuric acid and potassium permanganate, stirred in an ice bath for 0.8h-1.2h, reacted at 45°C-55°C for 8h-72h, placed in ice water, added with hydrogen peroxide and stirred continuously, and when bright yellow appears, allowed to stand for 45h-50h, the supernatant is discarded to obtain a lower precipitate, and the lower precipitate is washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and graphene oxide is obtained;

[0019] The graphene oxide is added to anhydrous ethanol, ultrasonically dispersed for 25 min-35 min, and then 3-(methoxy)propyltrimethoxysilane is added and magnetically stirred. After heating to 65° C.-75° C. in a water bath and keeping warm for 8 h-12 h, it is cooled to room temperature, filtered, and dried at room temperature for 45 h-50 h to obtain modified graphene.

[0020] Optionally, the step of using a fused deposition modeling method to print the hot-melt filament into an internally porous honeycomb structure comprises:

[0021] A model to be printed with a honeycomb structure is drawn and sliced, a printing rate and a slice thickness are determined, the hot-melt filament is placed in an FDM device, and printing is started according to the model to be printed to form an internal porous honeycomb structure.

[0022] Optionally, in the step of adding a nano-iron-loaded catalyst and persulfate, mixing, adding hydrogen peroxide, and conducting an oxidation reaction to obtain oxidative water production, the amount of the nano-iron-loaded catalyst added is 0.8 mg / L-1.2 mg / L, the amount of the persulfate added is 0.4 mg / L-0.8 mg / L, the amount of the hydrogen peroxide added is 0.06 mmol / L-0.09 mmol / L, the temperature of the oxidation reaction is 40°C-60°C, and the time of the oxidation reaction is 40 min-60 min.

[0023] Optionally, the persulfate is one or both of sodium persulfate and ammonium persulfate.

[0024] Optionally, the step of applying electricity to the oxidation water for electrolysis while continuously stirring and introducing air, and obtaining electrolytic water after the reaction is completed, comprises:

[0025] The oxidation water is electrolyzed at room temperature by applying a constant current of 200mA-300mA, with a current density of 40mA / cm 2 -75mA / cm 2 The electrolysis time is 1.2h-2.5h. The anode is a titanium-based ruthenium-iridium plated electrode plate, the cathode is a foam nickel electrode plate, the distance between the anode and the cathode is 1.8cm-2.2cm, and the magnetic stirrer is used to continuously stir at a speed of 450r / min-550r / min, and air is introduced at a flow rate of 45mL / min-55mL / min. After the reaction is completed, electrolytic water is obtained.

[0026] Optionally, the step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form natrolite precipitate, and filtering to obtain a treated solution and natrolite slag comprises:

[0027] The pH value of the electrolytic water is adjusted to 2.0-2.2, and the temperature is adjusted to 85°C-95°C. After reacting for 4.0h-4.5h, a precipitate of sodium ferroaluminate is formed. After filtering, a treated liquid and sodium ferroaluminate residue are obtained.

[0028] Optionally, after the step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form a precipitate of natto alum, filtering, and obtaining a treated solution and natto alum residue, the process further comprises:

[0029] The treated liquid is reused in the slurry mixing process as slurry mixing water;

[0030] The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

[0031] The present invention firstly allows the desulfurized water to be naturally sedimented, so that a large amount of suspended matter, impurities, etc. in the desulfurized water can be settled to the bottom, and the calcium ions in the desulfurized water can also be deposited to the bottom of the solution in the form of Ca(OH)2 under the action of gravity. After the sedimentation is completed, the supernatant is taken, and a large amount of suspended matter, impurities and most of the calcium ions in the desulfurized water can be removed without adding any new systems, equipment, or labor. Then, the nano-iron-loaded catalyst is used as a catalyst for hydrogen peroxide and persulfate at the same time, which can release Fe 2+ It catalyzes H2O2 to produce HO free radicals, degrades organic matter, and activates the persulfate system to promote the production of SO4 - · free radicals, further degrading organic matter, thus achieving dual catalytic oxidation degradation of organic matter based on the Fenton / persulfate oxidation system, and then through electrolysis reaction, under the action of external enhanced current, a potential difference is formed between the anode and the cathode, promoting the migration and transfer of ions in the solution in the electrolyte, forming a strong electrochemical reaction, thereby further mineralizing organic matter with high bond energy and difficult to degrade into carbon dioxide and water, and finally controlling the reaction conditions to make Fe 3+ With SO4 2- The reaction generates a stable sodium ferroaluminate precipitate, which is easier to settle than ferric hydroxide colloid and is more conducive to solid-liquid separation. The sodium ferroaluminate slag can be removed by filtration to achieve a large amount of Fe in the desulfurized water. 3+ The effective removal of ferric hydroxide can prevent it from forming iron hydroxide colloid in the subsequent slurry preparation process, and then adsorb and wrap the lithium in the solution, thereby increasing the Li2O content in the leachate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0033] Figure 1 This is a flow chart of the method for dual catalytic oxidation degradation of organic matter in desulfurized water described in an embodiment of the present application;

[0034] Figure 2 This is a diagram showing the phenomenon of desulfurized water embedded in slurry before and after the treatment described in the embodiments of the present application.

[0035] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0037] In view of the technical problems existing in the prior art, the embodiments of the present application provide a method for degrading organic matter in desulfurized water by dual catalytic oxidation, comprising the following steps:

[0038] After the desulfurized water is naturally settled, the supernatant is taken to obtain the impurity-removing liquid;

[0039] After adjusting the pH value of the impurity removal liquid to 3-4, adding the nano-iron supported catalyst and persulfate, mixing well, adding hydrogen peroxide, and performing an oxidation reaction to obtain oxidized water;

[0040] The oxidation-produced water is electrified for electrolysis while continuously stirred and air is introduced, and after the reaction is completed, electrolysis-produced water is obtained;

[0041] The pH value of the electrolytic water is adjusted to 2.0-2.2, and after the reaction forms natrona precipitate, it is filtered to obtain a treated liquid and natrona slag.

[0042] The present invention firstly allows the desulfurized water to be naturally sedimented, so that a large amount of suspended matter, impurities, etc. in the desulfurized water can be settled to the bottom, and the calcium ions in the desulfurized water can also be deposited to the bottom of the solution in the form of Ca(OH)2 under the action of gravity. After the sedimentation is completed, the supernatant is taken, and a large amount of suspended matter, impurities and most of the calcium ions in the desulfurized water can be removed without adding any new systems, equipment, or labor. Then, the nano-iron-loaded catalyst is used as a catalyst for hydrogen peroxide and persulfate at the same time, which can release Fe 2+ It catalyzes H2O2 to produce HO free radicals, degrades organic matter, and activates the persulfate system to promote the production of SO4 - · free radicals, further degrading organic matter, thus achieving dual catalytic oxidation degradation of organic matter based on the Fenton / persulfate oxidation system, and then through electrolysis reaction, under the action of external enhanced current, a potential difference is formed between the anode and the cathode, promoting the migration and transfer of ions in the solution in the electrolyte, forming a strong electrochemical reaction, thereby further mineralizing organic matter with high bond energy and difficult to degrade into carbon dioxide and water, and finally controlling the reaction conditions to make Fe 3+ With SO4 2- The reaction generates a stable sodium ferroaluminate precipitate, which is easier to settle than ferric hydroxide colloid and is more conducive to solid-liquid separation. The sodium ferroaluminate slag can be removed by filtration to achieve a large amount of Fe in the desulfurized water. 3+ The effective removal of ferric hydroxide can prevent it from forming iron hydroxide colloid in the subsequent slurry preparation process, and then adsorb and wrap the lithium in the solution, thereby increasing the Li2O content in the leachate.

[0043] As an implementation method of the present application, the step of taking the supernatant after the desulfurized water is naturally settled to obtain the impurity-removing liquid includes:

[0044] The desulfurized water is naturally settled at 5°C-35°C for 4h-8h, and after stratification, a supernatant liquid and a lower liquid are obtained by separation;

[0045] The lower layer liquid was stirred in reverse, and then naturally settled again at 5°C-35°C for 2h-4h. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid.

[0046] Specifically, through natural sedimentation, a large amount of suspended matter, impurities and calcium ions in the desulfurized water can be deposited to the bottom of the solution under the action of gravity. Preferably, the desulfurized water is naturally sedimented at 20° C., at which time the sedimentation rate of suspended matter and calcium ions is relatively high.

[0047] As an implementation method of the present application, the preparation steps of the nano-iron supported catalyst include:

[0048] The iron disulfide is pretreated, calcined at 700-800°C for 1h-1.5h, ball-milled at a speed of 180rpm / min-240rpm / min for 5h-7h, and dried to obtain nano iron disulfide particles;

[0049] The graphene is subjected to oxidation treatment and then subjected to derivatization and modification to obtain modified graphene;

[0050] The nano iron disulfide particles, the modified graphene and the polylactic acid are blended in a mass ratio of (1-2): (8-12): (3-5), dried at 110° C.-130° C. for 11 h-13 h, and then screw extruded to obtain a hot-melt filament;

[0051] The hot-melt filament is printed into a honeycomb structure with multiple internal pores by using a fused deposition modeling method, thereby obtaining the nano-iron-loaded catalyst.

[0052] Specifically, iron disulfide is an attractive catalyst for advanced oxidation reactions. It slowly releases ferrous ions through oxidation and dissolution in aqueous solution, allowing it to participate in advanced oxidation reactions as a sustainable iron source, avoiding the use of soluble iron salts and the formation of iron sludge, thereby preventing the desulfurized water after oxidation degradation from forming iron hydroxide colloids during slurry adjustment and adsorbing and encapsulating lithium. The oxidation and dissolution of iron disulfide also produces hydrogen ions, which is beneficial to maintaining favorable acidic conditions for advanced oxidation reactions. In addition, both ferrous ions and reduced sulfides can participate in redox reactions by acting as electron donors, thereby further enhancing their degradation of organic matter. However, iron disulfide dissolves slowly in water and has poor dispersibility. Therefore, the present application prepares nanometer-scale iron disulfide particles and loads them on modified graphene with a large specific surface area. Since graphene has a large specific surface area and good adsorption properties, and contains a large number of functional groups on the surface, the presence of these functional groups can generate electrostatic repulsion, thereby improving the dispersibility of nano iron disulfide particles in desulfurized water, and preparing it into a honeycomb structure, further enhancing its specific surface area, making it have abundant active sites and fully exposing the active sites, thereby accelerating the oxidation reaction.

[0053] The nano-iron supported catalyst of the present application can release Fe 2+ It catalyzes H2O2 to produce HO free radicals, thereby degrading organic matter. At the same time, it reacts chemically with water and hydrogen peroxide to provide the necessary acidic conditions for Fenton oxidation. The reaction formula is as follows:

[0054] 2FeS2+7O2+2H2O→2Fe 2+ +4SO4 2- +4H +

[0055] 2FeS2+15H2O2→2Fe3+ +14H2O+4SO4 2- +2H +

[0056] FeS2+14Fe3 + +8H2O→15Fe 2+ +2SO4 2- +16H +

[0057] In addition, the nano-iron supported catalyst of the present application can also activate the persulfate system and promote the production of SO4 - Free radicals further degrade organic matter. The reaction is as follows:

[0058]

[0059] Therefore, based on the Fenton / persulfate system of the present application, the nano-iron-supported catalyst can be used as a catalyst for both H2O2 and persulfate, thereby achieving dual catalytic oxidation degradation of organic matter.

[0060] In the specific implementation process, the step of pretreating iron disulfide includes:

[0061] The iron disulfide was crushed into particles by a crusher and passed through a 150-mesh sieve. The iron disulfide particles were then soaked in 10% HCl for 30 minutes to remove impurities such as the oxide layer on the surface of the iron disulfide particles. The particles were then rinsed with deionized water until neutral, and dried in an electric blast drying oven at 120° C. for 10 hours to obtain pretreated iron disulfide particles.

[0062] Since there are still some oxide layers on the surface of iron disulfide, it is necessary to immerse it in hydrochloric acid to destroy the oxide layers, which is beneficial to the release of Fe ions in iron disulfide.

[0063] Specifically, during ball milling, ethanol was used as a grinding aid, the grinding ball ratio was 20:1, and the ratio of ethanol to iron disulfide particles was 4 mL / 5 g.

[0064] As an implementation method of the present application, the step of oxidizing the graphene and then deriving and modifying it to obtain the modified graphene includes:

[0065] After stirring and mixing graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, the mixture is heated in an oil bath to 75°C-85°C and kept warm for 4.5h-5.5h, cooled to room temperature, filtered and washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and then the product is added to concentrated sulfuric acid and potassium permanganate, stirred in an ice bath for 0.8h-1.2h, reacted at 45°C-55°C for 8h-72h, placed in ice water, added with hydrogen peroxide and stirred continuously, and when bright yellow appears, allowed to stand for 45h-50h, the supernatant is discarded to obtain a lower precipitate, and the lower precipitate is washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and graphene oxide is obtained;

[0066] The graphene oxide is added to anhydrous ethanol, ultrasonically dispersed for 25 min-35 min, and then 3-(methoxy)propyltrimethoxysilane is added and magnetically stirred. After heating to 65° C.-75° C. in a water bath and keeping warm for 8 h-12 h, it is cooled to room temperature, filtered, and dried at room temperature for 45 h-50 h to obtain modified graphene.

[0067] Specifically, graphene is a nanoscale structure composed of carbon atoms in the form of sp 2 The planar film composed of hexagonal honeycomb lattices composed of hybrid orbitals has a large specific surface area and good adsorption properties, and can be used as a carrier of nano-iron disulfide to enhance the dispersibility of nano-iron disulfide in desulfurized water. However, since the lamellar graphene is easy to agglomerate, the present application breaks the large conjugated structure of graphene by oxidizing and grafting silane macromolecular chains on the surface of graphene, and effectively inhibits the irreversible stacking between graphene sheets, thereby significantly increasing the specific surface area of ​​the nano-iron-loaded catalyst and making it have abundant active sites.

[0068] As an implementable embodiment of the present application, the step of using a fused deposition modeling method to print the hot-melt filament into an internally porous honeycomb structure includes:

[0069] A model to be printed with a honeycomb structure is drawn and sliced, a printing rate and a slice thickness are determined, the hot-melt filament is placed in an FDM device, and printing is started according to the model to be printed to form an internal porous honeycomb structure.

[0070] The present application prepares the catalyst by means of fused deposition molding, and can directly prepare a nano-iron-loaded catalyst with an internal porous honeycomb structure in one step. By designing the internal porous and honeycomb structures, the overall geometric surface area of ​​the catalyst can be increased, thereby further increasing the active sites of the catalyst, thereby increasing the contact area between persulfate and hydrogen peroxide and the catalyst, accelerating the reaction of the Fenton / persulfate oxidation system, and promoting the degradation of organic matter.

[0071] As an implementation method of the present application, in the step of adding a nano-iron-loaded catalyst and a persulfate, mixing, adding hydrogen peroxide, and conducting an oxidation reaction to obtain oxidized water, the amount of the nano-iron-loaded catalyst added is 0.8 mg / L-1.2 mg / L, the amount of the persulfate added is 0.4 mg / L-0.8 mg / L, the amount of the hydrogen peroxide added is 0.06 mmol / L-0.09 mmol / L, the temperature of the oxidation reaction is 40°C-60°C, and the time of the oxidation reaction is 40 min-60 min.

[0072] Specifically, the COD content in the desulfurized water treated in this application is 18g / L-35g / L.

[0073] As an implementation method of the present application, the persulfate is one or both of sodium persulfate and ammonium persulfate.

[0074] As an implementation method of the present application, the step of applying electricity to the oxidation water for electrolysis while continuously stirring and introducing air, and obtaining electrolytic water after the reaction is completed, includes:

[0075] The oxidation water is electrolyzed at room temperature by applying a constant current of 200mA-300mA, with a current density of 40mA / cm 2 -75mA / cm 2 The electrolysis time is 1.2h-2.5h. The anode is a titanium-based ruthenium-iridium plated electrode plate, the cathode is a foam nickel electrode plate, the distance between the anode and the cathode is 1.8cm-2.2cm, and the magnetic stirrer is used to continuously stir at a speed of 450r / min-550r / min, and air is introduced at a flow rate of 45mL / min-55mL / min. After the reaction is completed, electrolytic water is obtained.

[0076] After the oxidation degradation by the Fenton / persulfate oxidation system, the oxidation products still contain some small molecular organic matter and difficult-to-degrade organic matter, whose bond energy is relatively large, and a lot of energy is required to completely mineralize them into carbon dioxide and water. At this time, through the electrolysis reaction, under the action of the external enhanced current, a potential difference is formed between the anode and the cathode, which promotes the migration and transfer of ions in the solution in the electrolyte, forming a strong electrochemical reaction, which can further mineralize the organic matter with high bond energy into carbon dioxide and water. In addition, the present application can further improve the degradation rate of organic matter by limiting the anode and cathode electrodes, current density and electrolysis time of the electrocatalytic oxidation process.

[0077] As an implementation method of the present application, the step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form a precipitate of natto alum, filtering, and obtaining a treated liquid and natto alum residue comprises:

[0078] The pH value of the electrolytic water is adjusted to 2.0-2.2, and the temperature is adjusted to 85°C-95°C. After reacting for 4.0h-4.5h, a precipitate of sodium ferroaluminate is formed. After filtering, a treated liquid and sodium ferroaluminate residue are obtained.

[0079] Specifically, Fe 3+ With SO4 2- Under the conditions of pH value of 1.7-1.9 and temperature of 85℃-95℃, yellow sodium ferroalcite precipitation can be formed. As can be seen from the following reaction formula, the amount of acid in the process of yellow sodium ferroalcite precipitation is increased. When 1g of iron is used to generate yellow sodium ferroalcite, about 1.75g ​​of sulfuric acid is released. Although the formation pH value of yellow sodium ferroalcite can be carried out at 1.7-1.9, sulfuric acid is continuously produced during the formation of ferroalcite, which will cause the pH value to drop continuously, and may cause iron ions and hydrogen ions or hydronium ions to form grass yellow ferroalcite. Grass yellow ferroalcite has poor sedimentation performance and is not conducive to removal by solid-liquid separation. Therefore, in order to ensure the continuity of formation and the thoroughness of iron removal, the present application controls the pH value to 2.0-2.2, and since a large amount of air is introduced during the electrolysis process, Fe in the electrolytic water can be reduced. 2+ Oxidized to Fe 3+ , SO3 2- Oxidized to SO4 2- Therefore, a large amount of Fe ions in the electrolytic water can be removed directly by controlling the pH value and temperature conditions of the sodium ferroaluminate precipitation.

[0080] Among them, the reaction formula for generating yellow sodium ferroaluminate precipitation is:

[0081] 3Fe 3+ +Na + +2SO4 2- +6H2O→NaFe3(SO4)2(OH)6+6H +

[0082] As an implementation method of the present application, after the step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form a precipitate of natto alum, filtering, and obtaining a treated liquid and natto alum residue, the method further includes:

[0083] The treated liquid is reused in the slurry mixing process as slurry mixing water;

[0084] The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

[0085] Specifically, the steps of preparing the polyferric sulfate flocculant include: adding sulfuric acid to the yellow sodium iron alum residue and mixing, performing microwave heating at a microwave frequency of 1500MHz-1800MHz for 10min-15min, then adding water and metallic iron to make the total iron concentration 200g / L-240g / L, and standing and aging at room temperature for 6h-8h, then adding hydrogen peroxide, reacting at 60℃-85℃ for 2h-4h, then adding ammonium sulfate, and waiting for Fe 3+ After the polymerized ferric sulfate precipitate is formed, it is filtered, washed and dried to obtain a polyferric sulfate flocculant. The present application uses sulfuric acid to dissolve the iron ions in the sodium iron alum residue, and uses a microwave heating method to decompose the sodium iron alum into sulfate, and then adds water and metallic iron for aging, and then uses an oxidant hydrogen peroxide to oxidize the divalent iron into trivalent iron. The addition of ammonium sulfate can dissociate into sulfate ions and ammonium ions in the aqueous solution to maintain the ion balance and pH value of the solution, promote the appropriate reaction of sulfate ions and trivalent iron ions, and promote Fe 3+ The precipitate of polyferric sulfate is formed by polymerization, thus realizing the recycling of natto alum residue.

[0086] The concentration of sulfuric acid is 1g / L-10g / L; yellow sodium iron alum residue and sulfuric acid are mixed at a solid-liquid mass ratio of 1: (2.5-4.5); the metal iron can be iron filings or iron flakes; the amount of hydrogen peroxide is 2+ The concentration is 120%-160%; ammonium sulfate can be added in an appropriate amount according to the rate of forming polyferric sulfate precipitation during the polymerization reaction of trivalent iron ions.

[0087] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0088] Example 1

[0089] A method for degrading organic matter in desulfurized water by dual catalytic oxidation, comprising the following steps:

[0090] The desulfurized water was naturally settled at 20°C for 6 hours, and after stratification, a supernatant and a lower layer were obtained by separation;

[0091] After the lower layer liquid was reversely stirred, it was naturally settled again at 20° C. for 3 hours. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid;

[0092] The iron disulfide was pretreated, calcined at 750°C for 1.2 hours, ball-milled at a speed of 210 rpm / min for 6 hours, and dried to obtain nano iron disulfide particles;

[0093] After graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide are stirred and mixed, the mixture is heated to 80°C in an oil bath and kept warm for 5 hours, then cooled to room temperature, filtered and washed until the pH value is 7.0, dried at room temperature for 47 hours, and then the product is added to concentrated sulfuric acid and potassium permanganate, stirred in an ice bath for 1 hour, reacted at 50°C for 35 hours, placed in ice water, and hydrogen peroxide is added and stirred continuously. When a bright yellow color appears, the mixture is allowed to stand for 47 hours, the supernatant is discarded, and a lower precipitate is obtained. The lower precipitate is washed until the pH value is 7, and dried at room temperature for 47 hours to obtain graphene oxide;

[0094] The graphene oxide was added to anhydrous ethanol, ultrasonically dispersed for 30 minutes, and then 3-(methoxy)propyltrimethoxysilane was added and magnetically stirred, and then heated to 70° C. in a water bath and kept warm for 10 hours, and then cooled to room temperature, and then filtered and dried at room temperature for 47 hours to obtain modified graphene;

[0095] The nano iron disulfide particles, the modified graphene and the polylactic acid are mixed in a mass ratio of 1.5:10:4, dried at 120° C. for 12 hours, and then screw-extruded to obtain a hot-melt wire material;

[0096] Drawing a model to be printed with a honeycomb structure and slicing it, determining a printing rate and a slice thickness, placing the hot-melt filament in an FDM device, and starting printing according to the model to be printed to form an internal porous honeycomb structure, thereby obtaining a nano-iron-loaded catalyst;

[0097] After the pH value of the impurity removal liquid is adjusted to 3, a nano-iron-loaded catalyst and sodium persulfate are added, mixed, and then hydrogen peroxide is added to perform an oxidation reaction at 50° C. The oxidation reaction time is 50 minutes to obtain oxidized water; wherein the amount of the nano-iron-loaded catalyst added is 1 mg / L, the amount of the sodium persulfate added is 0.6 mg / L, and the amount of the hydrogen peroxide added is 0.07 mmol / L;

[0098] A constant current of 250 mA was applied to the oxidized water for electrolysis at room temperature, and the current density was 57 mA / cm 2 The electrolysis time was 1.8 h. The anode was a titanium-based ruthenium-iridium plated electrode plate, the cathode was a nickel foam electrode plate, the distance between the anode and the cathode was 2.0 cm. The mixture was continuously stirred at a speed of 500 r / min by a magnetic stirrer, and air was introduced at a flow rate of 50 mL / min. After the reaction was completed, electrolytic water was obtained.

[0099] The pH value of the electrolytic water was adjusted to 2.1, and the temperature was adjusted to 90° C. After reacting for 4.2 hours, yellow sodium ferroalloy precipitate was formed, and after filtering, a treated liquid and yellow sodium ferroalloy slag were obtained;

[0100] The treated liquid is reused in the slurry mixing process as slurry mixing water;

[0101] The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

[0102] Specifically, when the untreated desulfurized water and the treated solution of this embodiment are respectively reused in the slurry preparation process, a large amount of foam appears after the untreated desulfurized water is embedded in the slurry preparation, and the color is yellowish, while the treated solution of this embodiment is embedded in the slurry preparation with inconspicuous foam and the color is white. Figure 2 shown.

[0103] Example 2

[0104] A method for degrading organic matter in desulfurized water by dual catalytic oxidation, comprising the following steps:

[0105] The desulfurized water was naturally settled at 5°C for 8 hours, and after stratification, a supernatant and a lower layer were obtained by separation;

[0106] After the lower layer liquid was reversely stirred, it was naturally settled again at 5° C. for 4 hours. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid;

[0107] The iron disulfide was pretreated, calcined at 700°C for 1.5 hours, ball-milled at a speed of 180 rpm / min for 7 hours, and dried to obtain nano iron disulfide particles;

[0108] After graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide are stirred and mixed, the mixture is heated to 75°C in an oil bath and kept warm for 5.5 hours, then cooled to room temperature, filtered and washed until the pH value is 6.8, dried at room temperature for 45 hours, and then the product is added to concentrated sulfuric acid, and potassium permanganate is added, stirred in an ice bath for 0.8 hours, reacted at 45°C for 72 hours, placed in ice water, and hydrogen peroxide is added and stirred continuously. When a bright yellow color appears, the mixture is allowed to stand for 45 hours, and the supernatant is discarded to obtain a lower precipitate, and the lower precipitate is washed until the pH value is 6.8, and dried at room temperature for 45 hours to obtain graphene oxide;

[0109] The graphene oxide is added to anhydrous ethanol, ultrasonically dispersed for 25 minutes, and then 3-(methoxy)propyltrimethoxysilane is added and magnetically stirred, and then heated to 65° C. in a water bath and kept warm for 12 hours, and then cooled to room temperature, and then filtered and dried at room temperature for 45 hours to obtain modified graphene;

[0110] The nano iron disulfide particles, the modified graphene and the polylactic acid are mixed in a mass ratio of 1:8:3, dried at 110° C. for 13 hours, and then screw-extruded to obtain a hot-melt wire material;

[0111] Drawing a model to be printed with a honeycomb structure and slicing it, determining a printing rate and a slice thickness, placing the hot-melt filament in an FDM device, and starting printing according to the model to be printed to form an internal porous honeycomb structure, thereby obtaining a nano-iron-loaded catalyst;

[0112] After adjusting the pH value of the impurity removal liquid to 3, adding nano-iron supported catalyst and ammonium persulfate, mixing, adding hydrogen peroxide, and performing oxidation reaction at 40° C. The oxidation reaction time is 40 minutes to obtain oxidation water; wherein the addition amount of nano-iron supported catalyst is 0.8 mg / L, the addition amount of ammonium persulfate is 0.4 mg / L, and the addition amount of hydrogen peroxide is 0.06 mmol / L;

[0113] A constant current of 200 mA was applied to the oxidized water for electrolysis at room temperature, and the current density was 40 mA / cm 2 The electrolysis time was 1.2 h. The anode was a titanium-based ruthenium-iridium plated electrode, the cathode was a nickel foam electrode, the distance between the anode and the cathode was 1.8 cm. The mixture was stirred continuously at a speed of 450 r / min by a magnetic stirrer, and air was introduced at a flow rate of 45 mL / min. After the reaction was completed, electrolytic water was obtained.

[0114] The pH value of the electrolytic water was adjusted to 2.0, and the temperature was adjusted to 85° C. After reacting for 4.5 hours, yellow sodium ferroalloy precipitate was formed, and after filtering, a treated liquid and yellow sodium ferroalloy slag were obtained;

[0115] The treated liquid is reused in the slurry mixing process as slurry mixing water;

[0116] The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

[0117] Example 3

[0118] A method for degrading organic matter in desulfurized water by dual catalytic oxidation, comprising the following steps:

[0119] The desulfurized water was naturally settled at 35°C for 4 hours, and after stratification, a supernatant and a lower layer were obtained by separation;

[0120] After the lower layer liquid was reversely stirred, it was naturally settled again at 35° C. for 2 hours. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid;

[0121] The iron disulfide was pretreated, calcined at 800°C for 1 hour, ball-milled at a speed of 240 rpm / min for 5 hours, and dried to obtain nano iron disulfide particles;

[0122] After stirring and mixing graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, the mixture was heated to 85°C in an oil bath and kept warm for 4.5 hours, then cooled to room temperature, filtered and washed until the pH value was 7.2, and dried at room temperature for 50 hours. The product was then added to concentrated sulfuric acid and potassium permanganate, stirred in an ice bath for 1.2 hours, reacted at 55°C for 8 hours, placed in ice water, and hydrogen peroxide was added and stirred continuously. When a bright yellow color appeared, the mixture was allowed to stand for 50 hours, and the supernatant was discarded to obtain a lower precipitate, and the lower precipitate was washed until the pH value was 7.2, and dried at room temperature for 50 hours to obtain graphene oxide;

[0123] The graphene oxide was added to anhydrous ethanol, ultrasonically dispersed for 35 minutes, and then 3-(methoxy)propyltrimethoxysilane was added and magnetically stirred, and then heated to 75° C. in a water bath and kept warm for 8 hours, and then cooled to room temperature, and then filtered and dried at room temperature for 50 hours to obtain modified graphene;

[0124] The nano iron disulfide particles, the modified graphene and the polylactic acid are blended in a mass ratio of 2:12:5, dried at 130° C. for 11 hours, and then screw-extruded to obtain a hot-melt wire material;

[0125] Drawing a model to be printed with a honeycomb structure and slicing it, determining a printing rate and a slice thickness, placing the hot-melt filament in an FDM device, and starting printing according to the model to be printed to form an internal porous honeycomb structure, thereby obtaining a nano-iron-loaded catalyst;

[0126] After adjusting the pH value of the impurity removal liquid to 4, adding nano-iron supported catalyst and sodium persulfate, mixing, adding hydrogen peroxide, and performing oxidation reaction at 60° C. for 40 minutes to obtain oxidized water; wherein the amount of nano-iron supported catalyst added is 1.2 mg / L, the amount of sodium persulfate added is 0.8 mg / L, and the amount of hydrogen peroxide added is 0.09 mmol / L;

[0127] A constant current of 300 mA was applied to the oxidized water for electrolysis at room temperature, and the current density was 75 mA / cm 2 The electrolysis time was 2.5 hours. The anode was a titanium-based ruthenium-iridium plated electrode plate, the cathode was a nickel foam electrode plate, the distance between the anode and the cathode was 2.2 cm, and the magnetic stirrer was used to continuously stir at a speed of 550 r / min, and air was introduced at a flow rate of 55 mL / min. After the reaction was completed, electrolytic water was obtained;

[0128] The pH value of the electrolytic water was adjusted to 2.2, and the temperature was adjusted to 95° C. After reacting for 4.0 hours, yellow sodium ferroalloy precipitate was formed, and after filtering, a treated liquid and yellow sodium ferroalloy slag were obtained;

[0129] The treated liquid is reused in the slurry mixing process as slurry mixing water;

[0130] The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

[0131] Comparative Example 1

[0132] Compared with Example 1, after the electrolytic water was prepared, the pH value of the electrolytic water was adjusted to 4, and after the Fe3+ was completely precipitated, it was filtered, and the pH value of the electrolytic water was adjusted to 8 to make Fe 2+ After the precipitation is complete, filter to obtain the treated liquid;

[0133] The treated liquid is reused as slurry mixing water in the slurry mixing process.

[0134] Comparative Example 2

[0135] Compared with Example 1, the nano-iron supported catalyst was replaced with ferrous sulfate, and the other steps remained unchanged.

[0136] Experimental Example 1

[0137] The suspended matter, COD and ammonia nitrogen content in the treatment liquid in the examples and comparative examples of the present application were detected, wherein the suspended matter content was detected with reference to the "Water Quality Suspended Matter Determination Gravimetric Method GB11901-89", the COD content was detected with reference to GB 11914 "Water Quality Chemical Oxygen Demand Determination Dichromate Method", and the ammonia nitrogen content was detected with reference to "Water Quality Ammonia Nitrogen Determination Gas Phase Molecular Absorption Spectrometry (HJ195-2023)". The test results are shown in Table 1 below.

[0138] Table 1

[0139] Group COD(g / L) COD removal rate (%) Desulfurized water 20.75 - Example 1 3.17 84.72 Example 2 3.78 81.78 Example 3 3.65 82.41 Comparative Example 1 3.85 82.44 Comparative Example 2 6.37 68.10

[0140] As can be seen from Table 1, after the desulfurized water is treated by the method of the present application, the COD content in the obtained treated liquid can be greatly reduced, and the COD removal rate can reach more than 80%, indicating that the treatment method of the present application can effectively degrade organic matter. In Comparative Example 1, the precipitation method is used to remove the Fe ions generated by electrolysis. Since the formed Fe(OH)3, Fe(OH)2 and other colloids have a flocculation effect, they can reduce COD by adsorbing part of the organic matter. Therefore, the COD removal rate in Comparative Example 1 can also reach more than 80%. In Comparative Example 2, ferrous sulfate is used to replace the nano-iron-loaded catalyst, and the catalytic activity of ferrous sulfate and the contact area with hydrogen peroxide and persulfate are much lower than those of the nano-iron-loaded catalyst, resulting in a much lower degree of organic degradation and a significantly lower COD removal rate than that in Example 1.

[0141] Experimental Example 2

[0142] After the untreated desulfurized water and the treated liquid of the embodiment and the comparative example were respectively reused in the slurry preparation process, the COD and Li2O contents in the obtained slurry preparation leachate were tested, and the lithium content in the obtained lithium slag was tested. The test results are shown in Table 2 below.

[0143] Table 2

[0144]

[0145] As can be seen from Table 2, after the desulfurized water is treated by the treatment method of the present application, the obtained treated liquid is embedded in the slurry, the COD of the leachate is significantly reduced, and the Li2O content in the leachate is increased, and the amount of lithium in the lithium slag also meets the process control requirements. Compared with the untreated desulfurized water directly used for embedding in the slurry, the treatment liquid of the present application can reduce the adsorption of lithium, reduce the amount of lithium in the lithium slag, and thus increase the Li2O content in the leachate. In Comparative Examples 1 and 2, due to the high iron content, more iron hydroxide colloids are produced during slurrying, thereby adsorbing and wrapping the lithium in the solution, and entering the lithium slag after pressing. Therefore, the total lithium, lithium, and β-lithium contents in the lithium slag indicators are generally high.

[0146] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made by using the contents of the present application specification and drawings under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A method for degrading organic matter in desulfurized water by dual catalytic oxidation, characterized in that: The following steps are involved: After the desulfurized water is naturally settled, the supernatant is taken to obtain the impurity-removing liquid; After adjusting the pH value of the impurity removal liquid to 3-4, adding the nano-iron supported catalyst and persulfate, mixing well, adding hydrogen peroxide, and performing an oxidation reaction to obtain oxidized water; The oxidation-produced water is electrified for electrolysis while continuously stirred and air is introduced, and after the reaction is completed, electrolysis-produced water is obtained; The pH value of the electrolytic water is adjusted to 2.0-2.2, and after the reaction forms natrona precipitate, it is filtered to obtain a treated liquid and natrona slag.

2. The method for degrading organic matter in desulfurized water by dual catalytic oxidation according to claim 1, characterized in that: The step of taking the supernatant after the desulfurized water is naturally settled to obtain the impurity-removing liquid comprises: The desulfurized water is naturally settled at 5°C-35°C for 4h-8h, and after stratification, a supernatant liquid and a lower liquid are obtained by separation; The lower layer liquid was stirred in reverse, and then naturally settled again at 5°C-35°C for 2h-4h. After separation, the supernatants obtained twice were combined to obtain a decontaminated liquid.

3. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 1, characterized in that: The preparation steps of the nano-iron supported catalyst include: The iron disulfide is pretreated, calcined at 700-800°C for 1h-1.5h, ball-milled at a speed of 180rpm / min-240rpm / min for 5h-7h, and dried to obtain nano iron disulfide particles; The graphene is subjected to oxidation treatment and then subjected to derivatization and modification to obtain modified graphene; The nano iron disulfide particles, the modified graphene and the polylactic acid are blended in a mass ratio of (1-2): (8-12): (3-5), dried at 110° C.-130° C. for 11 h-13 h, and then screw extruded to obtain a hot-melt filament; The hot-melt filament is printed into a honeycomb structure with multiple internal pores by using a fused deposition modeling method, thereby obtaining the nano-iron-loaded catalyst.

4. The method for degrading organic matter in desulfurized water by dual catalytic oxidation according to claim 3, characterized in that: The step of oxidizing the graphene and then deriving and modifying it to obtain modified graphene comprises: After stirring and mixing graphene, concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, the mixture is heated in an oil bath to 75°C-85°C and kept warm for 4.5h-5.5h, cooled to room temperature, filtered and washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and then the product is added to concentrated sulfuric acid and potassium permanganate, stirred in an ice bath for 0.8h-1.2h, reacted at 45°C-55°C for 8h-72h, placed in ice water, added with hydrogen peroxide and stirred continuously, and when bright yellow appears, allowed to stand for 45h-50h, the supernatant is discarded to obtain a lower precipitate, and the lower precipitate is washed until the pH value is 6.8-7.2, dried at room temperature for 45h-50h, and graphene oxide is obtained; The graphene oxide is added to anhydrous ethanol, ultrasonically dispersed for 25 min-35 min, and then 3-(methoxy)propyltrimethoxysilane is added and magnetically stirred. After heating to 65° C.-75° C. in a water bath and keeping warm for 8 h-12 h, it is cooled to room temperature, filtered, and dried at room temperature for 45 h-50 h to obtain modified graphene.

5. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 3, characterized in that: The step of using the fused deposition modeling method to print the hot-melt filament into an internally porous honeycomb structure comprises: A model to be printed with a honeycomb structure is drawn and sliced, a printing rate and a slice thickness are determined, the hot-melt filament is placed in an FDM device, and printing is started according to the model to be printed to form an internal porous honeycomb structure.

6. The method for degrading organic matter in desulfurized water by dual catalytic oxidation according to claim 1, characterized in that: In the step of adding the nano-iron-loaded catalyst and persulfate, mixing, adding hydrogen peroxide, and performing an oxidation reaction to obtain oxidized water, the amount of the nano-iron-loaded catalyst added is 0.8 mg / L-1.2 mg / L, the amount of the persulfate added is 0.4 mg / L-0.8 mg / L, the amount of the hydrogen peroxide added is 0.06 mmol / L-0.09 mmol / L, the temperature of the oxidation reaction is 40° C.-60° C., and the time of the oxidation reaction is 40 min-60 min.

7. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 1, characterized in that: The persulfate is one or both of sodium persulfate and ammonium persulfate.

8. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 1, characterized in that: The step of applying electricity to the oxidation water for electrolysis while continuously stirring and introducing air, and obtaining electrolytic water after the reaction is completed, comprises: The oxidation water is electrolyzed at room temperature by applying a constant current of 200mA-300mA, with a current density of 40mA / cm 2 -75mA / cm 2 The electrolysis time is 1.2h-2.5h. The anode is a titanium-based ruthenium-iridium plated electrode plate, the cathode is a foam nickel electrode plate, the distance between the anode and the cathode is 1.8cm-2.2cm, and the magnetic stirrer is used to continuously stir at a speed of 450r / min-550r / min, and air is introduced at a flow rate of 45mL / min-55mL / min. After the reaction is completed, electrolytic water is obtained.

9. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 1, characterized in that: The step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form natto alum precipitate, filtering to obtain a treated solution and natto alum slag comprises: The pH value of the electrolytic water is adjusted to 2.0-2.2, and the temperature is adjusted to 85°C-95°C. After reacting for 4.0h-4.5h, a precipitate of sodium ferroaluminate is formed. After filtering, a treated liquid and sodium ferroaluminate residue are obtained.

10. The method for dual catalytic oxidation degradation of organic matter in desulfurized water according to claim 1, characterized in that: After the step of adjusting the pH value of the electrolytic water to 2.0-2.2, reacting to form natto alum precipitate, filtering to obtain the treated liquid and natto alum slag, the method further comprises: The treated liquid is reused in the slurry mixing process as slurry mixing water; The sodium ferric alum residue is recovered and used to prepare a polyferric sulfate flocculant.

Citation Information

Patent Citations

  • Sulfur modified porous iron oxide catalyst, preparation method therefor and application of sulfur modified porous iron oxide catalyst

    CN105413713A

  • Electro-Fenton catalyst and preparation method and application thereof

    CN112295573A

  • Method and system for treating pharmaceutical wastewater through micro-electrolysis coupled photo-Fenton oxidation

    CN115367934A

  • Method for purifying lithium in leachate

    CN118419956A

  • Method for recovering lithium from acid clinker

    CN118563123A